2021
DOI: 10.4314/sokjvs.v19i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in gills and liver of Clarias gariepinus fingerlings exposed to acute concentrations of dry cell battery

Abstract: Waste dry cell batteries are frequently improperly disposed and subsequently washed into water bodies-- causing deleterious effects on fish particularly Clarias gariepinus which inhabits diverse freshwater habitats. Acute toxicity of water-soluble fractions of waste dry cell batteries was investigated on C. gariepinus fingerlings under laboratory conditions in 96 hours. Ten (10) C. gariepinus fingerlings were exposed to acute concentrations (0.31, 0.63, 1.25, 2.50, and 5.00 g/L) of waste dry cell batteries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Also,Rahmanet al [64] detected severe necrosis, appearance of large number of vacuoles in cytoplasm and pyknotic nuclei in the liver of Channa punctatus and Anabas testudineus after intoxication of diazinon. Furthermore, Fernando et al [65] reported that, nuclear level impact of bispyribac-sodium on the fish, Poecilia reticulate was significantly higher number of damaged nuclei in liver tissue was noted in herbicide exposed fish Similar findings are compatible with the recorded histopathological lesions, which revealed a notable degeneration and necrosis of hepatocytes coincided with increasing in ASAT and ALAT activities [66][67][68][69] and confirming that, it may be attributed to liver injury [70][71].…”
Section: Discussionsupporting
confidence: 56%
“…Also,Rahmanet al [64] detected severe necrosis, appearance of large number of vacuoles in cytoplasm and pyknotic nuclei in the liver of Channa punctatus and Anabas testudineus after intoxication of diazinon. Furthermore, Fernando et al [65] reported that, nuclear level impact of bispyribac-sodium on the fish, Poecilia reticulate was significantly higher number of damaged nuclei in liver tissue was noted in herbicide exposed fish Similar findings are compatible with the recorded histopathological lesions, which revealed a notable degeneration and necrosis of hepatocytes coincided with increasing in ASAT and ALAT activities [66][67][68][69] and confirming that, it may be attributed to liver injury [70][71].…”
Section: Discussionsupporting
confidence: 56%
“…About 1kg of dried leaves was pulverized into a fine powder, sieved with a 30 µm mesh size sieve, and stored in an airtight polythene bag. After the determination of definitive concentrations of the plant material through preliminary range finding tests, the powder of each definitive concentration was weighed using a weighing machine (Mettler Toledo PB602 model), and the stock solution of each concentration was prepared by macerating in 1L of dechlorinated municipal water for 24 hours [24]. The mixture was filtered through a funnel chocked with non-absorbent cotton wool into the appropriate experimental tanks for a 96hr acute exposure test.…”
Section: Collection Preparation Maceration and Preparation Of Stock S...mentioning
confidence: 99%
“…Preliminary range-finding tests [26] were conducted to determine the definitive concentrations of the leaf extract of T. peruviana that could cause 50% mortality in C. gariepinus juveniles. A Series of preliminary trials [26] was conducted on 27 C. gariepinus juveniles in three test tanks labeled A, B, and C. Each test tank was stocked with three (3) C. gariepinus juveniles and exposed to different concentrations of the leaf extract in three experimental trials, after which acute test concentrations of 0.63, 1.25, 2.50, 5.00, and 10.00g/L of the leaves extract of T. peruviana were determined as the definitive acute concentrations.…”
Section: Procedures For Conducting Acute Toxicity Testmentioning
confidence: 99%
“…Prior to the administration of the crude fruit extract to the experimental fish, preliminary experimental trials (Audu, Omirinde, Gosomji & Wazhi, 2017) 30 were carried out to determine suitable concentrations for the experiment. Subsequent to series of experimental trials 5 concentrations (2.00, 2.50, 3.00, 3.50 and 4.00g/L) of crude fruit extract of B. aegyptiaca were determined as definitive sedative concentrations.…”
Section: Preparation Of Definitive Sedative Concentrations Of Pulveri...mentioning
confidence: 99%
“…(2017) 30 . The results of the current study however revealed longer induction and recovery times of C. gariepinus fingerlings.…”
Section: Phytochemical Screening Of Crude Fruit Of B Aegyptiacamentioning
confidence: 99%